The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1806-9061-2016-0327
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Dietary Threonine Levels on Optimal Growth Performance and Intestinal Morphology in 1-14 Days Old Ross 308 Broilers

Abstract: SummARyThis experiment was carried out to evaluate the effects of four levels of dietary threonine (Thr) supplementations on growth performance, gut size and histomorphometric alterations of small intestines in broiler chicks in 1-14 days. Two hundred eighty-eight Ross 308 one-day-old male broiler chicks were randomly assigned to four treatments with six replicates (12 birds per replication) received a common diet based on corn, wheat and soybean meal that met nutrients requirement of Ross 308. Birds were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
3
6
0
Order By: Relevance
“…The findings of this study indicated that threonine has significant effects on intestinal villi, crypt depth, and intestinal mucin production. The values found for villus height are similar to those reported by Najafi et al (2017), who studied dietary levels of threonine and found the height of villi in the duodenum ranging from 1350.33 to 1551.67 μm, and below the values found by Ospina-Rojas et al (2013), who identified a maximum value of 1782 μm for villus height in the duodenum.…”
Section: Discussionsupporting
confidence: 88%
“…The findings of this study indicated that threonine has significant effects on intestinal villi, crypt depth, and intestinal mucin production. The values found for villus height are similar to those reported by Najafi et al (2017), who studied dietary levels of threonine and found the height of villi in the duodenum ranging from 1350.33 to 1551.67 μm, and below the values found by Ospina-Rojas et al (2013), who identified a maximum value of 1782 μm for villus height in the duodenum.…”
Section: Discussionsupporting
confidence: 88%
“…Threonine (Thr; 2-amino-3-hydroxybutyric acid, C 4 H 9 NO 3 ) is an essential amino acids in broilers which is known for its crucial role in gastro-intestinal tract (GIT) structure and function, mucin secretion and γ-globulin production (Corzo et al 2007, Canogullari et al 2009, Ayasan and Okan 2014. It is an important constituent of mucin, a major glycoprotein which protects the intestinal epithelium from injury and maintains intestinal immune function (Najafi et al 2017, Rasheed et al 2018. Because of its high demand, a larger proportion of the dietary Thr ingested is often catabolizes at the intestinal level for synthesis of intestinal-mucosal proteins and digestive secretions for optimum nutrient break-down, absorption and utilization (Corzo et al 2007, Sigolo et al 2017.…”
mentioning
confidence: 99%
“…Because of its high demand, a larger proportion of the dietary Thr ingested is often catabolizes at the intestinal level for synthesis of intestinal-mucosal proteins and digestive secretions for optimum nutrient break-down, absorption and utilization (Corzo et al 2007, Sigolo et al 2017. In addition, Thr exerts an efficient immunomodulatory effect through enhancement of antibody production (Najafi et al 2017). In view of these benefits, therefore, IOF of Thr on may exert positive influence on enteric development and immunomodulatory effect in broilers through enhancement of antibody production.…”
mentioning
confidence: 99%
“…Isoleucine is one of branched chain amino acid which play a major role in enhancing glucose consumption and utilization by upregulating intestinal and muscular glucose transporters (Zhang et al, 2017). Threonine is widely used for poultry feed in case to optimalization of growth state and intestinal development morphology (Najafi et al, 2017). Feng et al (2013) also reported that threonine improved growth, digestive and absorption capacity, and enterocyte proliferation and differentiation in juvenile Jian carp.…”
Section: Methodsmentioning
confidence: 99%